Malignant Fungating Wounds of the Head and Neck: Management and Antibiotic Stewardship. Issue 1 (February 2022) - O'Neill, Liam; Nelson, Zach; Ahmad, Nadir; Fisher, Alec H.; Denton, Ana; Renzi, Michael; Fraimow, Henry S.; Stanisce, Luke
Objective: Malignant fungating wounds (MFWs) are unfortunate and underreported manifestations of some advanced head and neck cancers. The management of MFWs is complex and challenging. MFWs are often mistaken for infectious processes/abscesses and treated indiscriminately with oral or intravenous antibiotics. Our aim is to promote awareness of MFWs and provide education on their management. We summarize their cost-effective and evidence-based therapies and highlight antibiotic stewardship with respect to their management. Data Sources: A literature review was performed of PubMed, Cochrane Review, SCOPUS, Embase, and Google Scholar databases regarding topical and systemic treatments for MFWs. Review Methods: Full-text articles were identified with the following terms: fungating, ulcerative, wound, tumor, malignancy, antibiotics, topical, dressings, radiotherapy, head, neck, scalp, face, lip, and ear. Treatment recommendations were extrapolated, categorically summarized, and retrospectively assigned with an evidence level based on the GRADE system (Grading of Recommendations, Assessment, Development, and Evaluation). Conclusions: In the absence of systemic signs and symptoms of infections, MFWs should not be treated as conventional infections or abscesses, with prophylactic oral or intravenous antibiotics. Topical treatments such as ointments and wound dressings are the mainstay in terms of managing the unsightly appearance and fetid odor from these entities. Implications for Practice: MFWs are most often not amenable to definitive/curative surgical or nonsurgical therapy, but consultation with a head and neck oncologic specialist will help to determine if the underlying malignancy requires surgery, radiation therapy, or palliative treatment.